Knee flexor moments during propulsion in cycling. A creative solution to Lombards Paradox - Gregor, R. J.; Cavanagh, P. R.; LaFortune, M. (Journal of Biomechanics, 1985)
The function of two joint muscles in the human lower extremity was studied during a cycling task with efficiency of their action discussed in light of Lombard's Paradox. Special pedals were designed to monitor reaction forces parallel to the sagittal plane of the body. Net moments of force about the hip, knee and ankle and EMG patterns in selected lower extremity muscles were recorded in five subjects pedalling against a constant load. The most original aspect of this study was the clear difference in hip and knee action during the propulsive phase of the pedalling cycle. A knee flexor moment was consistently observed in all subjects starting approximately half way through the propulsive phase of crank rotation (0-180°) and presented as a creative solution to Lombard's Paradox.